Explaining Declining Rates of Institutional LTC Use in the Netherlands: A Decomposition Approach. (March 2015) - de Meijer, Claudine; Bakx, Pieter; van Doorslaer, Eddy; Koopmanschap, Marc
Abstract: The use of long‐term care (LTC) is changing rapidly. In the Netherlands, rates of institutional LTC use are falling, whereas homecare use is growing. Are these changes attributable to declining disability rates, or has LTC use given disability changed? And have institutionalization rates fallen regardless of disability level, or has LTC use become better tailored to needs? We answer these questions by explaining trends in LTC use for the Dutch 65+ population in the period 2000–2008 using a nonlinear variant of the Oaxaca–Blinder decomposition. We find that changes in LTC use are not due to shifts in the disability distribution but can almost entirely be traced back to changes in the way the system treats disability. Elderly with mild disability are more likely to be treated at home than before, whereas severely disabled individuals continue to receive institutional LTC. As a result, LTC use has become better tailored to the needs for such care. This finding suggests that policies that promote LTC in the community rather than in institutions can effectively mitigate the consequences of population aging on LTC spending. Copyright © 2015 John Wiley & Sons, Ltd.